Special populations: vulnerability and protection - DOI: 10.3395/reciis.v2.Sup1.207en - Wendy Rogers; Angela Ballantyne (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
Research with vulnerable participants raises a number of challenging issues for researchers and ethical review committees. Vulnerability arises when participants are relatively powerless compared with researchers. This may be due to extrinsic factors such as poverty or lack of education, or intrinsic factors such as severe illness or intellectual disability. Vulnerable participants risk increased harm from research because they are unable to protect their interests. This article provides examples of research with vulnerable populations and describes in detail ways in which researchers and ethical review committees can work to decrease the risks of harm for these groups. Also, the article presents a discussion of sharing research benefits fairly, and describes four conditions for ethical research with vulnerable participants.